IL-17A and IL-17F induce an invasive phenotype in human rheumatoid synoviocytes through the same signaling pathway and the CXCR4/SDF1 axis. (22nd February 2011) - Hot, Arnaud; Miossec, Pierre
Abstract : Objective: IL-17A is implicated in rheumatoid arthritis (RA) pathogenesis; but the contribution of IL-17F remains to be clarified. This report analyses the effects IL-17A versus IL-17F on gene expression, signaling and invasiveness in human RA synoviocytes. Methods: The comparison between IL-17A and F effects on RA synoviocytes was assessed at the mRNA level by microarrays (Affymetrix U133 +2). Western blotting, qRT-PCR, and DNA binding assay were used to evaluate their signaling pathways. The capacities of IL-17A and F alone or in combination with TNF to induce synoviocyte migration and invasion were tested using transwell Matrigel invasion chambers. A functional DNA binding assay was used to evaluate the regulation of Hypoxia Induced Factor 1 (HIF1-α) activation. Results: In microarrays, IL-17A and IL-17F alone had very similar but not identical regulatory effects, IL-17F being less active, with a synergistic pattern in the presence of TNF. This synergistic effect was linked in part to the enhancing expression of TNF RII by IL-17A and F. Regarding their signaling pathway, virtually all IL17A and F inducible genes were dependent on NF-κB activation, whereas a minor number was modulated by p38. Hypoxia-induced pathway was activated by IL-17A and F. Among the hypoxia-induced genes, IL-17A and F alone or combined with TNF induced CXCR4 mRNA (289 fold for IL17A, 34 fold for IL-17F, 450 fold for the combination of IL-17A with TNF). Over expression of CXCR4 at the surface of synoviocytes was confirmed by IF staining. IL-17A and TNF induced in synergy synoviocyte migration and invasion through CXCR4 (6 vs 67 migrated cells/HPF, p≤0.05). Blockade of CXCR4 decreased synoviocyte migration (− 10 fold, p<0.05). The combination of IL-17A or F with TNF induced activation of HIF1-α under normoxic conditions (2 fold, p=0.003). Conclusion: When combined with TNF, IL-17A and F induced very similar but not identical expression pattern in RA synoviocytes, may contribute to the progression of RA through increased synoviocyte aggressiveness. Part of this effect results from a mediated CXCR4/SDF1 pathway. These results are in line with IL-17A and F targeting in RA.